2019
DOI: 10.1111/os.12584
|View full text |Cite
|
Sign up to set email alerts
|

SuperPATH Minimally Invasive Approach to Total Hip Arthroplasty of Femoral Neck Fractures in the Elderly: Preliminary Clinical Results

Abstract: Objective To investigate the clinical efficacy and advantages of the SuperPATH minimally invasive approach to total hip arthroplasty in the treatment of femoral neck fractures in the elderly. Methods From January 2016 to September 2018, 110 cases of elderly patients with femoral neck fractures were included in the present study. According to the method of operation, the patients were divided into two groups for comparison. There were 55 cases of the SuperPATH minimally invasive approach to total hip arthroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…To further read the full text, we found a lack of required data in 9 pieces of literature and 3 pieces of literature included other irrelevant interventions. Finally, 6 articles [10][11][12][13][14][15]were selected. The PRISMA literature inclusion and exclusion process were shown in Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To further read the full text, we found a lack of required data in 9 pieces of literature and 3 pieces of literature included other irrelevant interventions. Finally, 6 articles [10][11][12][13][14][15]were selected. The PRISMA literature inclusion and exclusion process were shown in Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Based on the available datum from 4 studies [10,11,14,15], we found signi cant heterogeneity (Chi² = 111.20, df = 3, I² = 97%, p < 0.00001). As was shown in Fig.…”
Section: Incision Lengthmentioning
confidence: 89%
See 3 more Smart Citations